Integrating the Values of Tawhid as the Foundation for the Development of Science and Technology in the Society 5.0 Era - Surtimah Surtimah; Adam Adam; Nuritam; Luthfiyah Luthfiyah; Zuhrah Zuhrah (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to examine the nature of Science, Technology, and the Arts from an Islamic perspective through ontological, epistemological, and axiological approaches. It seeks to identify the concept of integration between revelation, reason, and empirical experience in establishing a paradigm for Science, Technology, and the Arts in Islam, and to analyze the role of the values of tawhid in guiding the development and utilization of Science, Technology, and the Arts so that they remain oriented toward the welfare of humanity. This study employs a library research method with a descriptive qualitative approach, through an analysis of various relevant literature. The results of the study indicate that, ontologically, Islam views reality as a unity of the material and spiritual grounded in Tawhid. Epistemologically, the sources of knowledge revelation, reason, and empirical experience are integrative and mutually complementary. Axiologically, science and technology are directed toward human welfare and a balanced life based on ethical and spiritual values. The concept of integrating revelation, reason, and empirical experience grounded in tawhid serves as the foundation of Islamic epistemology in constructing a holistic, balanced paradigm of science and technology oriented toward human welfare, both materially and spiritually. The role of tawhid as both the foundation and ethical safeguard in the development of science and technology ensures that knowledge remains rooted in divine values and directed toward the welfare and justice of all humanity.